2010
DOI: 10.1182/blood-2010-02-268375
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma activation enhances bortezomib sensitivity

Abstract: IntroductionMantle cell lymphoma (MCL) is an aggressive, incurable B-cell malignancy that makes up 5% to 10% of non-Hodgkin lymphoma (NHL) cases. 1 Patients with MCL typically present with extensive lymph node involvement as well as extranodal dissemination within the spleen, bone marrow, and gastrointestinal tract. Treatment with conventional cytotoxic agents produces high initial response rates, but the outcome of patients with MCL remains among the poorest of all NHL subtypes with a median overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Importantly, unlike CSCs that have been identified in other malignancies, there have been no surface antigens identified that could isolate and enrich for MCLs and other mature pre-germinal center B cell malignant cells [65]. The ALDH + MCL cells were observed to be relatively quiescent and resistant to the standard chemotherapeutic agents used for MCL patients, including dexamethasone (anti-inflammatory steroid), etoposide (topoisomerase II inhibitor), and bortezomib (proteasome inhibitor).…”
Section: Aldh Plays a Self-protective Role In Normal Stem Cells And Cscsmentioning
confidence: 96%
See 2 more Smart Citations
“…Importantly, unlike CSCs that have been identified in other malignancies, there have been no surface antigens identified that could isolate and enrich for MCLs and other mature pre-germinal center B cell malignant cells [65]. The ALDH + MCL cells were observed to be relatively quiescent and resistant to the standard chemotherapeutic agents used for MCL patients, including dexamethasone (anti-inflammatory steroid), etoposide (topoisomerase II inhibitor), and bortezomib (proteasome inhibitor).…”
Section: Aldh Plays a Self-protective Role In Normal Stem Cells And Cscsmentioning
confidence: 96%
“…Moreb, et al observed that pre-treatment of bone marrow cells with IL-1 and TNF-α for 6 to 20 hours resulted in an increase in ALDH1 mRNA and protein levels [105], and that this ultimately leads cellular protection against 4-HC [104]. Since then, it has been determined that high cytosolic ALDH1A1 or ALDH3A1 activity in normal cells [106,107], stem cells [44], and cancer stem cells [65,74] confers resistance to therapy in preclinical model systems. The majority of these studies focused on alkylating agents such as CP and other oxazaphosphorines [13-16, 45, 78, 87, 88, 100-104, 106-110].…”
Section: Aldh Plays a Self-protective Role In Normal Stem Cells And Cscsmentioning
confidence: 98%
See 1 more Smart Citation
“…63 The existence of such a population has been conclusively demonstrated in chronic myeloid leukemia (CML) and acute myeloid leukemia (AML), and there is accumulating evidence for their existence in other hematologic and solid tumors, such as myeloma, lymphoma, glioblastoma, breast, and prostate cancer. 16,18,[64][65][66][67] In these malignancies, CSCs are predominantly quiescent and therefore resistant to conventional therapeutic approaches. Failure to effectively target these cells results in residual low-level disease and the likelihood of future relapse.…”
Section: Malignant Stem Cellsmentioning
confidence: 99%
“…The protective efects of ALDH for CSCs may also include the inhibition of downstream apoptosis-related pathways [18,23,24]. ALDH-positive CSCs have also demonstrated resistance to myriad chemotherapeutic agents such as anthracyclines and taxanes [25,26], two classes of drugs commonly used in OS treatment. ALDH-positive cancer cells develop this drug resistance in part because of their increased ability to metabolize certain drugs into their nontoxic byproducts [27].…”
Section: Osteosarcoma -Biology Behavior and Mechanisms 34mentioning
confidence: 99%